The Mathematics Communication Skill Reviewed from Self-Efficacy on Group Investigation Learning with Demonstration Feedback - Kurniawan, Deni; Kartono, Kartono; Suyitno, Hardi (Universitas Negeri Semarang, 2021)
This research aims to describe the mathematics communication skill of learners reviewed from self-efficacy on Group Investigation learning with demonstration feedback. This research used the mixed method with concurrent embedded design. The research population was from the seventh grade of Islam Sultan Agung JHS 4 Semarang 2019/2020. The subjects were two selected people of high, moderate, and low categories. The research collected the data with a mathematics communication test, self-efficacy questionnaire, and interview. The results showed the Group Investigation learning with demonstration feedback positively influenced the learners’ mathematics communication skills. The other results described the learners’ mathematics communication skills of each category: high, moderate, and low. They had various mathematics communication skill indicator mastery.